Exploring Causes of Difficulties in Learning Linear Algebra - Subedi, Abatar (Innovative Research Journal, 2025)
This paper aims to explore causes of difficulties while learning linear algebra course at master level and find possible ways to mitigate these difficulties. I applied case study methods and selected two cases responded purposively. I used semi-structured interview guidelines and performance test to explore the causes of difficulties and used general inductive approach to analyze the data. The result shows that the students at master level are experiencing linear algebra course difficult for conceptual and procedural understanding because of having poor English language, unavailability of appropriate learning resources, having poor perquisites, abstract nature of concepts, unable to construct examples and counter examples, and the nature of the curriculum. These difficulties can mitigate by developing strong prerequisites before introducing new concepts, using examples of abstract concepts, choosing varieties of techniques of proofs for theorems, connecting abstraction with real-life examples, and other software and videos of the concepts in linear algebra while teaching and learning at master level.